2008
DOI: 10.1080/17451000802270346
|View full text |Cite
|
Sign up to set email alerts
|

Size and age-dependent changes of escape response to predator attack in the Queen scallopAequipecten opercularis

Abstract: To cite this Article Schmidt, Maike, Philipp, Eva E. R. and Abele, Doris(2008)'Size and age-dependent changes of escape response to predator attack in the Queen scallop Aequipecten opercularis ',Marine Biology Research,4:6,[442][443][444][445][446][447][448][449][450] To link to this Article: DOI: 10.1080/17451000802270346 URL: http://dx.doi.org/10.1080/17451000802270346Full terms and conditions of use: http://www.informaworld.com/terms-and-conditions-of-access.pdf This article may be used for research, teachi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…We observed no difference in clap rate, but found that nearly 50% of young scallops closed their shells completely and for as long as 30 min following the predator attack. By contrast, just 3% of the bigger individuals behaved in this way and the majority remained permanently open or opened the shells again within the 30 min experimental observation (Schmidt et al, 2008).…”
Section: Introductionmentioning
confidence: 88%
“…We observed no difference in clap rate, but found that nearly 50% of young scallops closed their shells completely and for as long as 30 min following the predator attack. By contrast, just 3% of the bigger individuals behaved in this way and the majority remained permanently open or opened the shells again within the 30 min experimental observation (Schmidt et al, 2008).…”
Section: Introductionmentioning
confidence: 88%
“…However, this question remains to be answered. Similarly, despite a large number of studies on scallop escape responses (Ansell et al, 1998;Bailey and Johnston, 2005;Cheng et al, 1996;Himmelman et al, 2009;Perez et al, 2009;Schmidt et al, 2008;Stephens and Boyle, 1978;Thomas and Gruffydd, 1971), little is known about their ETs. Analysis of the escape response in the vertical plane shows it comprises three phases: take-off, level swimming and sinking (Ansell et al, 1998).…”
Section: Molluscsmentioning
confidence: 99%
“…Reznick et al, 2004;Bronikowski et al, 2006) or decoupling of performance following metamorphosis in amphibians (Johansson et al, 2010). In scallops, changes in both muscle physiology and escape response performance with age and size have been observed (Tremblay et al, 2006;Phillipp et al, 2008;Schmidt et al, 2008;Lebrecque and Guderley, 2011).…”
Section: The Journal Of Experimental Biology 216 (17)mentioning
confidence: 99%
“…The adductor may be divided into two regions; the smooth-fibre tonic muscle region is used for ventilation of the mantle during periods of resting, whilst the larger striated-fibre phasic muscle region, which can repeatedly and rapidly contract, is exclusively used during the escape response (Fleury et al, 2005;Pérez et al, 2008). Because of the ease with which the escape response can be recorded, we have learnt much about the muscle physiology underlying the contractile and recovery phases of the escape response and how the magnitude of the escape response relates to parameters such as stress (Jenkins and Brand, 2001), age/size Schmidt et al, 2008;Labrecque and Guderley, 2011), temperature , reproductive state (Brokordt et al, 2000a;Brokordt et al, 2000b;Kraffe et al, 2008;Pérez et al, 2009), genotype and diet . As a well-studied taxa, individual differences in scallop escape response performance have been reported and repeat measures of known individuals compared over time (using paired t-tests or repeated measures ANOVA depending on the number of repeat measures being compared) have enabled the degree to which individual performance is consistent over time to be examined (e.g.…”
Section: Introductionmentioning
confidence: 99%